Uncovering the mechanistic basis of Rheum palmatum L. (rhubarb) in the treatment of chronic kidney disease: an integrative approach using network pharmacology, molecular docking, and experimental validation - Wenjing He; Zhen Wei; Siwei Li; Songji Han; Jing Ma; Lei Wu; Dan Lu; Guang Ta (Pharmaceutical Biology)
Context Rheum palmatum L. (Rhubarb) has shown potential in managing Chronic Kidney Disease (CKD) but its protective mechanisms remain unclear.Objective This study investigates rhubarb’s therapeutic effects and underlying mechanisms in CKD.Materials and methods High-performance liquid chromatography (HPLC) established a rhubarb fingerprint to ensure quality control. Network pharmacology and Mendelian randomization identified primary CKD therapeutic targets. Inflammation, oxidative stress, and renal performance were assessed through ELISAs and biochemical tests. Renal structure and fibrosis were examined using hematoxylin-eosin and Masson staining. Protein expression related to fibrosis, apoptosis, and NF-κB pathway activity was measured via Western blotting. Discovery Studio 2019 (DS 2019) was used for molecular docking.Results HPLC fingerprinting confirmed high batch-to-batch consistency of rhubarb, identifying five key anthraquinones (aloe-emodin, rhein, emodin, chrysophanol, physcion) with similarity indices >0.91. Network pharmacology identified 19 active compounds targeting 2,597 CKD-related proteins, with 47 overlapping targets including IL6, TNF, TP53, CASP3, and IL1B as core nodes. MR analysis demonstrated a statistically significant causal association between TNF and CKD (OR = 1.02, p < 0.05), with positive trends for IL6 and CASP3. In CKD rat models, rhubarb significantly improved renal function by reducing blood urea nitrogen (BUN), serum creatinine (SCr), and uric acid (UA) levels (p < 0.05). Histopathology showed reduced glomerulosclerosis, tubular atrophy, interstitial fibrosis, and inflammatory infiltration after treatment. Rhubarb markedly decreased renal fibrosis markers including collagen I, collagen III, α-SMA, and TGF-β (p < 0.01). Pro-inflammatory cytokines IL-6, IL-1β, and TNF-α levels were significantly suppressed (p < 0.001). Antioxidant enzyme activities of superoxide dismutase (SOD) and glutathione peroxidase (GSH-Px) were restored, while lipid peroxidation (LPO) was reduced (p < 0.05). Rhubarb inhibited NF-κB pathway activation by lowering phosphorylated NF-κB and IκBα, and increasing total IκBα expression (p < 0.01). Apoptosis-related proteins showed upregulated Bcl-2 and downregulated Bax and cleaved caspase-3 expression (p < 0.05). Molecular docking confirmed strong binding affinities of rhubarb’s core compounds with key targets such as TNF and IL6, supporting their therapeutic roles.Conclusion Rhubarb significantly reduces renal impairment, fibrosis, inflammation, and apoptosis through the NF-κB pathway, supporting its traditional use and potential as an adjunct therapy for CKD.